2003
DOI: 10.1159/000070301
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor D Is Associated with Lymph Node Metastasis in Human Colorectal Carcinoma

Abstract: Objective: Expression of vascular endothelial growth factor (VEGF)-D by tumors is associated with metastasis to lymph nodes in mice. However, there are few reports concerning the clinical significance of VEGF-D protein in human carcinoma. Methods: After confirming production of VEGF-D by eight colorectal carcinoma cell lines, we investigated relationships between the expression of VEGF-D protein, lymph node metastasis and postoperative survival in 83 colorectal carcinoma patients. mRNA levels in cell lines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
0
20
0
3
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) has been nominated as one of the triggers of angiogenesis. VEGF expression has also demonstrated a strong association with the presence of lymph node metastasis [41,42]. Moreover, VEGF stimulation reportedly causes increased expression of survivin [43].…”
Section: Discussionmentioning
confidence: 98%
“…Vascular endothelial growth factor (VEGF) has been nominated as one of the triggers of angiogenesis. VEGF expression has also demonstrated a strong association with the presence of lymph node metastasis [41,42]. Moreover, VEGF stimulation reportedly causes increased expression of survivin [43].…”
Section: Discussionmentioning
confidence: 98%
“…VEGF-D is up-regulated in breast [86], colorectal [87], gastric [79], and thyroid [88] carcinomas, cervical intraepithelial neoplasia [89], glioblastoma [90], and melanoma [91]. Its expression correlates with lymph node metastasis in colorectal [92], lung [93], and ovarian carcinomas [94]. VEGF-D signaling thus represents a potential anti-cancer and antimetastasis target.…”
Section: Vegf-dmentioning
confidence: 99%
“…A recent study by Orlandini et al [13] demonstrated that β-catenin was a negative regulator of VEGF-D mRNA stability, therefore VEGF-D expression might only be responsible for the nodal metastatic behavior in tumors that have lost or reduced expression of β-catenin. In addition, there was apparent discrepancy of VEGF-D expression in tumors reported by different authors [14][15][16][17][18] . Thus, here we only investigate the role of VEGF-C in promoting lymph node metastasis in gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%